Evaluation of Anticardiolipin Antibodies and Lupus Erythematosus Cell in Type 2 Diabetes Nigerian Population - Odeyinka Odewusi; Afanyi Abbey; Olalere Obadire; Olayinka Olaniyan; Oluwadamilola Ogunyemi; Emmanuel Omon (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aim. Diabetes mellitus, a chronic medical disorder characterized by persistent elevation blood glucose and, glycosuria together with its most common co morbidity still have so many mysteries that needs unravelling. This study was thus designed to evaluate serum anticardiolipin antibodies and the presence of lupus erythematosus cell in both treated and untreated uncomplicated and complicated type 2 diabetes. Methods. This study included 26 uncomplicated type 2 diabetes subjects, 15 were treated, 11 were untreated (newly diagnosed) and 31 complicated type 2 diabetes subjects, 17 were on treatment, 14 were untreated (newly diagnosed) and the remaining 17 were apparently healthy individuals which served as control. A total of 74 subjects were thus assessed. Determinations of blood pressure, Plasma glucose, BMI and anticardiolipin antibodies (ACA) was carried out on all subjects and the values seen in each of the groups compared with one another, however, this study also assessed the effect of treatment, gender and age on all estimated parameters. Results obtained were subjected to statistical analysis using Statistical Package for Social Sciences version 23 (SPSS 23). All parameters were expressed as mean ± SD, ANOVA was the tool of choice in comparing means and values were statistically significant at p<0.05. Results. Fasting blood glucose was significantly higher in treated and untreated uncomplicated and complicated type 2 diabetes with hypertension when compared to control respectively. In uncomplicated and complicated type 2 diabetes with hypertension, body mass index was significantly increased when treated and untreated were compared to control respectively. Lupus erythematosus test positivity of 5.8% and 7.1% were seen in treated complicated and untreated complicated diabetes respectively. Anticardiolipin antibody was also significantly higher in treated and untreated uncomplicated and complicated diabetics compared to control respectively. ACA was still higher in untreated compared to treated diabetics. Conclusion. This research found that ACA hence the likelihood of antiphospholipid syndrome is associated with type 2 diabetes mellitus. This can be more serious if there is vascular complication or when diabetes and its complications are poorly managed.